Measles vaccines and non-specific effects on mortality or morbidity: A systematic review and meta-analysis - Louise A. Fournais; Anne C. Zimakoff; Andreas Jensen; Jeppe H. Svanholm; Ingvild Fosse; Lone G. Stensballe (PLoS ONE, 2025)
Background This review evaluates the hypothesis of beneficial non-specific effects of the standard-titre measles vaccine. Methods We conducted a systematic review and meta-analysis of randomised controlled trials. Trials included standard or high-titre live attenuated measles containing vaccines compared to other vaccines or placebo. The primary outcomes were mortality and morbidity. Secondary outcomes were infections, antibiotic use, atopy, allergies, asthma, and atopic dermatitis. Findings 23 articles were included in this systematic review. Mortality: Two doses of measles vaccine vs. only one dose showed no significant effect on mortality; risk ratio (RR) = 1.05 (95% CI: 0.78 to 1.41), p = 0.76. The analysis was based on a relative risk reduction (RRR) of 25% and a control group event rate of 2.32% as measured in the actual trials included in the analysis. In males, the association was rejected: RR = 1.09 (0.86 to 1.37), p = 0.47. In females, the association was not rejected at 25%,but was at 33% level: RR = 1.0 (0.64 to 1.54), p = 0.99. Morbidity: Overall, the hypothesis was rejected: RR = 0.94 (0.80 to 1.10), p = 0.43. The rejection was sustained for both sexes: females RR = 0.95 (0.77 to 1.18), p = 0.6; males RR = 0.92 (0.83 to 1.03), p = 0.13. Interpretation Based on evidence from randomised controlled trials, this systematic literature review and meta-analysis did not support the hypothesis of non-specific effects of standard-titre measles containing vaccines. Trial Sequential Analysis indicated that the meta-analysis included sufficient data to reach this conclusion. Trial registration PROSPERO CRD42022344473